2015
DOI: 10.1097/dcr.0000000000000292
|View full text |Cite
|
Sign up to set email alerts
|

Does Extended Surgery Influence Health-Related Quality of Life in Patients With Rectal Cancer?

Abstract: This study showed no major differences between patients undergoing total mesorectal excision surgery and those receiving extended surgery, with the exception of body image, which was significantly lower in patients <70 years undergoing extended surgery. In all patient groups, treatment for rectal cancer influenced sexual activity dramatically. Awareness of the impact of surgery on health-related quality of life and sexuality is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…The rate of sexual inactivity among women in the APER population was high (71%), in accordance with previous studies . This could be due in part to age and relationship status, and a similar trend was seen in the reference population, but several studies have reported a significant decrease in sexual activity after rectal cancer treatment .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The rate of sexual inactivity among women in the APER population was high (71%), in accordance with previous studies . This could be due in part to age and relationship status, and a similar trend was seen in the reference population, but several studies have reported a significant decrease in sexual activity after rectal cancer treatment .…”
Section: Discussionsupporting
confidence: 89%
“…By clinical experience and review of previous literature [3,4,6,[8][9][10]19,20] the following variables were identified as potential risk factors for urogenital dysfunction 3 years after APE and were included in the statistical analysis: age, sex, marital status, comorbidity, ASA, (neo)adjuvant (chemo)radiotherapy, preoperative urogenital dysfunction, surgical method, extent of surgery, postoperative infection, local recurrence and stomarelated worries (only used in analysis for sexual dysfunction).…”
Section: Risk Factors For Urogenital Dysfunctionmentioning
confidence: 99%
“…Regarding HRQL after surgical resection for rectal cancer, two Dutch studies reported lower physical function and sexual function in older patients than younger patients [ 49 , 50 ]. However, a previous German study of 253 patients with rectal cancer reported both better sexual function and worse physical function, role function and global quality of life in older patients after surgical resection [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…35 Estimates of the incidence of sexual dysfunction in RC survivors varies from 23%–69% in men and 19%–62% in women. 6 In a population-based study (N=21,802), 25.1% of RC survivors reported sexual dysfunction, and 13.9% reported difficulties with appearance and body image.…”
Section: Introductionmentioning
confidence: 99%